Study on the Binding Interaction of the α,α′,δ,δ′-Tetramethylcucurbit[6]uril With Biogenic Amines in Solution and the Solid State - Yang, Liguo; Kan, Jinglan; Wang, Xin; Zhang, Yonghui; Tao, Zhu; Liu, Qingyun; Wang, Fang; Xiao, Xin (Frontiers in Chemistry, 2018)
1H NMR spectroscopy and MALDI-TOF mass spectrometry were utilized to examine the binding interaction of α,α′,δ,δ′-tetramethylcucurbit[6]uril (TMeQ[6]) and six biogenic amines (spermine, spermidine, 2-phenethylamine, tyramine, histamine, and tryptamine). Their 1H NMR spectra both at pD = 7 and pD = 3 revealed that four biogenic amines (spermine, spermidine, 2-phenethylamine, and histamine) can fit in the TMeQ[6] cavity respectively, and other biogenic amines were located outside of the TMeQ[6] portal. In addition, a solid-state evaluation with single-crystal X-ray diffraction analysis showed the binding interaction of spermine, spermidine, 2-phenethylamine, and tyramine with TMeQ[6].